2016
DOI: 10.1016/j.colsurfb.2016.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Role of chemical crosslinking in material-driven assembly of fibronectin (nano)networks: 2D surfaces and 3D scaffolds

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Nonetheless, hydrogels with up to 2 wt% ethylene glycol dimethacrylate could still achieve the same results as those previously seen on 2D surfaces. [128] It has also been demonstrated that plasma polymerized PEA, a production technique with more translational potential, can produce similar results. [93] This approach was recently tested to coat polyimide tube implants, which provide a bioinert mechanical support for long bone fracture healing.…”
Section: Platforms With Inclusion Of Ecm Componentsmentioning
confidence: 93%
See 3 more Smart Citations
“…Nonetheless, hydrogels with up to 2 wt% ethylene glycol dimethacrylate could still achieve the same results as those previously seen on 2D surfaces. [128] It has also been demonstrated that plasma polymerized PEA, a production technique with more translational potential, can produce similar results. [93] This approach was recently tested to coat polyimide tube implants, which provide a bioinert mechanical support for long bone fracture healing.…”
Section: Platforms With Inclusion Of Ecm Componentsmentioning
confidence: 93%
“…This has been the strategy explored in a series of works using poly(ethyl acrylate) (PEA) as a base polymer. [93,[127][128][129] Mechanistically, FN adsorption onto PEA promotes its spontaneous fibrillar reorganization, a process that has been termed "material-driven FN fibrillogenesis," while adsorption on other polymers results in retention of a globular conformation. This fibrillary conformation leads to a rearrangement of FN chains and simultaneous exposure of affinity-binding regions for both integrins and GFs.…”
Section: Platforms With Inclusion Of Ecm Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding macromolecules adsorption process is of major significance in a variety of fields, such as surface treatment, lubrication, the pharmaceutical and cosmetic industries as well as in biological processes and biophysics . The adsorption of macromolecules (e.g., proteins) on biomaterials such as polymers, ceramics, or metals is of paramount importance for tissue engineering and regenerative medicine applications . Furthermore, knowledge of the structural formation at the solid/liquid interface is also a key factor in designing micro/nanostructures with promising applications in nanotechnology …”
Section: Introductionmentioning
confidence: 99%